Determination of Capital Structure Culture of Banking Companies Using Indonesia's Macroeconomic Context - Rinaldy Saleh; Isnurhadi Isnurhadi; Shelfi Malinda; Marlina Widiyanti (International Journal Labs, 2024)
Capital structure is an important company funding decision, especially for companies in developing countries. Apart from that, capital structure shows the combination of various funding methods managed by the company, where the way a company finances is very relevant for investors, directors and all other stakeholders. Thus, funding decisions have a direct influence on company value. There is an argument about how mixing debt and assets in a capital structure impacts a company's value. Furthermore, the determining factors that can have an influence on a company's capital structure are still debated in financial studies. This study uses leverage as the dependent variable in the 2013-2022 period by examining 30 banking company objects in Indonesia listed on the Indonesia Stock Exchange using STATA V.17 to answer the panel data analysis of this research. The financial ratios reviewed are the liquidity ratio, The era of volatility, growth opportunities, bank size and external macroeconomic variables where inflation and Gross Domestic Product (GDP) are the basis of companies' problems in financing their capital structure. The results show that banks in Indonesia have high leverage, where each business company applies differences in its finances. Return on assets, growth opportunity, inflation show a positive and significant relationship with leverage on debt and assets. Profit volatility, tangibility, bank size and Gross Domestic Product show a negative and significant relationship. In terms of research, the research has limitations which are expected to include all banking companies in Indonesia and add external macroeconomic variables to further identify capital structure values ??such as exchange rates and interest rates.